Sponsoring sportowy a organizowanie centrów transferu wiedzy - Cieśliński, Wojciech; Murdza, Krzysztof; Witkowski, Kazimierz (Sport sponsorship and organization of centers of knowledge transfer, 2005)
The issues concerning the system of knowledge transfer in the process of sport sponsorship management were presented in the paper. Sport sponsorship is the process of psychological game (battle) between the sponsor and the beneficiary institution, which in the final phase must be accomplished by a mutual compromise. The aim of such a game is to find an ideal business solution, suitable for both sides. This is an indispensable requirement for implementation of sponsorship. The process of sponsorship as a game in the field of non-material resources optimizing access to knowledge may be described with the help of phenomenology. Thus in the article, phenomenology was presented as a method of knowledge description taking into consideration basic processes of its flow in centers of knowledge transfer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 31-37